1967
DOI: 10.1126/science.158.3802.790
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine in the Carotid Body of the Cat

Abstract: Glomus cells, at least in the carotid body of cats, contain catechol and indolamines. Cells containing adrenaline, noradrenaline, and 5-hydroxytryptamine were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1968
1968
1986
1986

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Glomus cells in vivo contain several putative neurotransmitters, including norepinephrine , dopamine, and serotonin (5,10). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Glomus cells in vivo contain several putative neurotransmitters, including norepinephrine , dopamine, and serotonin (5,10). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition evoked by dopamine was reduced during SP infusions whereas that associated with 5-HT was potentiated. It was not possible to determine what was responsible for these effects, nor what effect SP was having on the release of dopamine or 5-HT, both of which are present in the carotid body (Chiocchio, Biscardi & Tramezzani, 1967;Chiocchio, King, Carballo & Angelacos, 1971). It has been shown in cats that intra-nigral SP results in an increased release of dopamine (Ch6ramy, Niedullon, Michelot & Glowinski, 1977) and, in rats, that SP injected into the lateral ventricles stimulates the synthesis and utilization of dopamine and 5-HT in brain (Carlsson, Magnusson, Fisher, Chang & Folkers, 1977).…”
mentioning
confidence: 99%
“…Some authors have indicated that catecholamines may not have a significant role in chemoreceptor function (Eyzaguirre & Koyano, 1965;Eyzaguirre & Zapata, 1968;Zapata et al, 1969), although other evidence indicates otherwise (Biscoe, 1965;Sampson, 1972;Andrew, Black, Comroe & Jacobs, 1972). A physiological role for 5-hydroxytryptamine (5-HT) may not be discarded, since the carotid body contains a certain amount of 5-HT (Chiocchio et al, 1967(Chiocchio et al, , 1971; furthermore, histochemical methods have shown that 5-HT is located in the electron-dense core vesicles of the Type I cells (Chiocchio et al, 1967;I-Li Chen et al, 1967). These findings lend some support to the view that 5-HT may have some functional role in the carotid body.…”
Section: Introductionmentioning
confidence: 99%
“…A physiological role for 5-hydroxytryptamine (5-HT) may not be discarded, since the carotid body contains a certain amount of 5-HT (Chiocchio et al, 1967(Chiocchio et al, , 1971; furthermore, histochemical methods have shown that 5-HT is located in the electron-dense core vesicles of the Type I cells (Chiocchio et al, 1967;I-Li Chen et al, 1967). These findings lend some support to the view that 5-HT may have some functional role in the carotid body.…”
Section: Introductionmentioning
confidence: 99%